2012
DOI: 10.4269/ajtmh.2012.11-0660
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Anemia and Its Risk Factors Among Children 6–36 Months Old in Burma

Abstract: Abstract. Anemia is a common nutritional problem, and it has a remarkably high prevalence rate in Southeast Asia. In this study, children from 6 to 36 months were investigated to determine (1) the prevalence of anemia and (2) risk factors associated with anemia. Convenience sampling was used to select three villages in three different regions in Burma. Hemoglobin and anthropometric indicators were measured for 872 children. Logistic regression analyses were used to determine factors associated with anemia. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

43
82
4
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(130 citation statements)
references
References 9 publications
43
82
4
1
Order By: Relevance
“…The preliminary questionnaire testing was completed in a previous study. 7 Anthropometric measurements [height, weight, head circumference (HC), and mid-upper arm circumference (MUAC)] were collected during the fieldwork. The Infant/Child Shorrboard (Electronic baby scale, RSP-2060B; Xianyang Huachao Co. Ltd., Shanxi, China) was used to measure child stature, recumbent infant length (if the child was < 85 cm), and weight (with infants/children's clothing and shoes removed).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The preliminary questionnaire testing was completed in a previous study. 7 Anthropometric measurements [height, weight, head circumference (HC), and mid-upper arm circumference (MUAC)] were collected during the fieldwork. The Infant/Child Shorrboard (Electronic baby scale, RSP-2060B; Xianyang Huachao Co. Ltd., Shanxi, China) was used to measure child stature, recumbent infant length (if the child was < 85 cm), and weight (with infants/children's clothing and shoes removed).…”
Section: Methodsmentioning
confidence: 99%
“…A high prevalence of malnutrition was found in this survey, similar to our previous reports in 2012. 7 Both early and late introduction of CFs led to a higher risk of malnutrition; however, the health effects were different.…”
Section: -26mentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have found significant relationships of anaemia with lower growth and developmental indicators in children of different ages (6,7,8). The exact mechanism by which IDA impairs growth has not been elucidated yet.…”
Section: Introductionmentioning
confidence: 99%
“…Several herbal based nutraceutical products are available in market to prevent chronic diseases. Moringa oleifera, belonging to the family Moringaceae is one such plant which grow fast and found to be widely distributed in India 5 . The plant is renowned for its medical properties 6 and it is used as antispasmodic, stimulant, expectorant, antifertility, anticancer, hepatoprotectivity, antiulcer, and diuretic agent 7 .…”
Section: Introductionmentioning
confidence: 99%